2018
DOI: 10.1111/gcbb.12567
|View full text |Cite
|
Sign up to set email alerts
|

Economic and environmental performance of miscanthus cultivated on marginal land for biogas production

Abstract: Environmental issues surrounding conventional annual biogas crops have led to growing interest in alternative crops, such as miscanthus. In addition to the better environmental performance, miscanthus can be grown on marginal land where no competition with feed and food crops is anticipated. On marginal land however, biomass yields are significantly lower than on good agricultural land. This raises the question of the economic and environmental sustainability of miscanthus cultivated on marginal land for bioga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 63 publications
(110 reference statements)
0
71
0
Order By: Relevance
“…On the one hand, regions with a high share of unused grassland cultivate PBC without changing the production. For these regions, the implementation of PBC with a special focus on marginal land could be useful (Wagner et al, ). On the other hand, regions with an already intensive grassland utilization further increase this intensity of utilization.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, regions with a high share of unused grassland cultivate PBC without changing the production. For these regions, the implementation of PBC with a special focus on marginal land could be useful (Wagner et al, ). On the other hand, regions with an already intensive grassland utilization further increase this intensity of utilization.…”
Section: Discussionmentioning
confidence: 99%
“…Perennial lignocellulose crops, such as miscanthus, switchgrass and poplar, are suitable for lands with such constraints because genotypes have been identified that are tolerant to abiotic stresses (e.g., drought, salinity, cold) frequently occurring on marginal land (Clifton‐Brown et al, ; Lewandowski et al, ). However, Wagner et al () conclude that careful assessment of the specific prevailing conditions should be performed because biodiversity may be higher in some marginal lands under their existing vegetation than under PBC. PBC can have an environmentally beneficial performance. They only require soil cultivation once in a plantation lifetime of about 20 years, in the establishment phase.…”
Section: What Are the Current Status Of And Future Perspectives For Smentioning
confidence: 99%
“…It can be provided from sustainable forestry and from agricultural production, with agricultural residues and perennial biomass crops (PBC) being the most favourable resources (Clifton‐Brown et al, ; Fabbrini et al, ; Hoeber et al, ). PBC can be integrated into existing farming systems using less favourable land or land marginal for food crop production, with the additional provision of various ecological benefits (Wagner et al, ).…”
Section: Conclusion—perspectives For Integrated Lignocellulosic Valuementioning
confidence: 99%
“…The substitution of 1 GJ of the marginal German electricity mix for instance, which was used as the fossil reference, results in a carbon mitigation potential of 934 kg CO 2 eq. (Wagner et al, ). In addition, Kiesel et al () compared the environmental performance of biogas produced using maize and miscanthus as substrate.…”
Section: Substratesmentioning
confidence: 99%
“…They reduce the risks of biomass production because they deliver more stable yields over the years than annual crops, which are more influenced in their establishment and growth by precipitation and temperature conditions (Ehmann, Bach, Laopeamthong, Bilbao, & Lewandowski, 2017;Lewandowski, 2016). Both Wagner et al, (2019) and Mangold, Lewandowski, & Kiesel (2019a) take up this point of positive ecological effects of alternative substrates in their contributions and exemplify it with miscanthus. Although miscanthus has so far mainly been used for heat production and material applications, targeted use in biogas plants can also be important in the context of taking ecological effects into account, especially as the methane hectare yields of miscanthus can keep up with those of silage maize .…”
Section: Substratesmentioning
confidence: 99%